Collective public transport and unequal access to the city: a study of the districts of the Far North region of Campos dos Goytacazes, Rio de Janeiro, Brazil - Priscila Freitas da Silva; Santos, Leandro Bruno (Geografares, 2023)
The issue of urban mobility and accessibility is particularly important in a city with such a fragmented territorial organization as Campos dos Goytacazes-RJ, where public transport is an essential service. This article analyses the access to Campos dos Goytacazes for the inhabitants of the northernmost part of the municipality. Qualitative and quantitative methods were used to carry out this analysis, and the results of this study highlight the need for an effective urban transport and accessibility policy, taking into account the unique territorial organization of the municipality of Campos dos Goytacazes.